THIN FILM TECHNOLOGY IN THE FIELD OF ENVIRONMENT - Gupta, Vinod Kumar; Shrivastava, S.B.; Bhatia, Geeta (International Journal of Research -GRANTHAALAYAH, 2015)
Environmental conservation is a challenge to the mankind. The measures to check it must be easy to use, cheap and eco friendly. Thin film technology is providing answers to some of these problems. Nanostructured thin films of metal oxide are used in solar cells, semi permeable membrane, protective coatings, electronic devices, optoelectronics etc. Recently thin films have been developed to be used in different fields of environment. These include gas sensors, nanofilters etc. A brief review of the work done in this field is given in this paper.